An analysis of speech styles used by two characters in the movie Green Book - Hummaira Hummaira; Dohra Fitrisia; Kismullah Abdul Muthalib (Universitas Syiah Kuala, 2022)
This study analyzes the different speech styles used by two characters in the movie Green Book. The characters are Tony Lip, a white driver, and Dr. Shirley, a black musician. The objectives of this study are to find out the types of speech styles used by the two characters and to find out the differences in the speech styles used. The source of data in this study is the movie script. Descriptive-qualitative method is selected to analyze the data. Joos’ theory (1967) was applied in this research, which concerns the five types of speech styles including frozen, formal, consultative, casual, and intimate styles. The result of this research shows that Tony Lip only used four types of speech styles: formal, consultative, casual, and intimate. Tony Lip dominantly used casual speech style, whereas formal style is the least frequent. Dr. Shirley used all five types of speech styles. Consultative speech style is the most commonly used by Dr. Shirley, whereas frozen speech style is the least frequent